Skilling for the Future: Evaluating Post-Reform Status of â€œSkilling Pakistanâ€ and Identifying Success Factors for Tvet Improvement in the Region - Chamadia, Sumaira; Shahid, & Muhammad (Journal of Technical Education and Training, 2018)
Technical and vocational education plays a pivotal role in mobilizing the wheels of the nation towards development and prosperity and hence itâ€™s inevitably important to focus on enhancing the quality of education provided in TVET institutes. Considering the huge skills gap Pakistan has initiated a five-year reform support program in 2011 to transform the current TVET system proposed by National skills strategy. This study hence aims to evaluate the outcomes of the reform support program through field verification and taking inputs from the major stakeholders. The case study approach with single embedded design in which different polytechnic institutions operated under government, private sector and Non-Governmental Organisations were used as unit of analysis sharing the same contextual situations. The findings show that despite getting the support from the international donor agencies and prudently strategized policies, the government has not been successful in achieving the desired outcomes of the reform support program. The success factor identified that could thrive the TVET sector is the strong coalition among all the stakeholders including government, private sector and employersâ€™ federation.